Outcomes of surgical practice on tubo-ovarian abscess in an academic hospital - Sezgin, Burak; Akın, Melike Nur; Kasap, Burcu (The European Research Journal, 2021)
Objectives: We aimed to analyseour experience in the surgical management of tubo-ovarian abscess at a tertiary hospital. Methods: Data from patients who underwent laparoscopy or laparotomyfor treatment of tubo-ovarian abscess were retrospectively analyzed. The clinical and surgical outcomes of patients with tubo-ovarian abscess were compared according to the applied surgical approach. Results: The mean largest diameter of the abscess in the laparoscopy and laparotomy groups were similar (p = 0.520). The mean day for total antibiotic use was significantly shorter in the laparoscopy group (10.00 ± 4.37 day vs 17.91 ± 6.59 day; p = 0.002). All cases in the laparotomy group needed to change the antibiotic regimen, but it was needed only in 28.58% of patients in the laparoscopy group. However, preoperative fever and pulse rate was significantly higher in laparotomy group than in the laparoscopy group (p = 0.004, p = 0.014; respectively). There was no statistical difference in terms of applied surgical procedure betweenthetwo groups. The most applied surgical procedure was abscess drainage in both of the groups (71.42%, 90.90%; respectively). The median operation time in patients with laparoscopy was statistically shorter than in patients with laparotomy (65.50 [58-93] minutes vs 84 [74-90] minutes, p = 0.048). In comparison of postoperative complications between two groups, there was no statistically significant difference. We observed statistically significant declination in white blood cell count and C-reactive protein values at the postoperative 7th day in all patients (p < 0.001 and p < 0.001, respectively). Conclusions: In terms of surgical approach for tubo-ovarian abscess, laparoscopy is more effective than laparotomy for shorter duration of postoperative antibiotic use, operation time and length of hospital stay.